Response and toxicity of donor lymphocyte infusions following T cell depleted non-myeloablative allogeneic hematopoietic stem cell transplantation from 3–6/6 HLA matched donors - Rizzieri, David A (2008)
BACKGROUND: We report the outcome of early donor lymphocyte infusions (DLI) following T-cell depleted non-myeloablative transplantation using stem cells from human leukocyte antigen (HLA) matched or mismatched donors. PATIENTS AND METHODS: Sixty-nine patients with high risk hematologic malignancies received DLI following fludarabine, cyclophosphamide, and alemtuzumab with infusion of stem cells from a matched sibling (52) or partially matched family member donor (17). Patients received the first infusion a median of 50 days following transplant and doses ranged from 1×10(4) CD3+ cells/kg to 3.27 ×10(8) CD3+ cells/kg, depending on clinical status and physician’s discretion. A median cell dose of 1× 10(5) CD3+ cells/kg in the mismatched setting and 1×10(6) CD3+ cells/kg in the matched sibling setting appears safe with only 1/7 (14%) and 4/31 (13%) respectively experiencing severe aGVHD at these doses. Importantly, 38% of patients with persistent disease prior to DLI attained a remission following infusion. Nine of the 69 remain alive and disease free 32–71 months following the first DLI infusion. CONCLUSION: Low doses of DLI can be safely provided soon after T-cell depleted non-myeloablative therapy and provide a chance of remission. However, long term survival still remains poor due primarily to relapse in these patients however.